Author Response: Precise Staging of Lymphoma during Pregnancy Using MRI is Not Always Crucial. (March 2015) - Lavi, Noa; Netanel, A Horowitz; Brenner, Benjamin
Response to: van Dam LR, Han SN, Dierickx D, Amant F. Optimal staging of lymphoma during pregnancy is crucial. Womens Health 11(2), 101–102 (2015).